2015
DOI: 10.1007/s13760-015-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug adherence of patients with epilepsy in Iran: the effects of the international economic sanctions

Abstract: Drug adherence of patients with epilepsy was investigated to determine the reasons behind poor adherence. In this retrospective chart review study, all patients with a clinical diagnosis of epilepsy were recruited at the outpatient epilepsy clinic at Shiraz University of Medical Sciences. We routinely asked about the patient's drug adherence and reasons behind poor drug adherence in every office visit. We defined drug adherence adequate if the patient reported less than or equal to one missed dose per month. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…Asadi-PooyaAA. [19] A retrograde chart reviewing to investigate the effects of sanctions on drug adherence among patients with epilepsy Reduction in drug adherence was close to being signi cant (P = 0.07) before and after 2012; despite some drugs were unavailable after sanctions, and others were much more expensive. Medicine subsidization by the government seems to play an important role.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Asadi-PooyaAA. [19] A retrograde chart reviewing to investigate the effects of sanctions on drug adherence among patients with epilepsy Reduction in drug adherence was close to being signi cant (P = 0.07) before and after 2012; despite some drugs were unavailable after sanctions, and others were much more expensive. Medicine subsidization by the government seems to play an important role.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, ten out of eleven included studies addressed the effects of sanctions on access to medicine in Iran. Three articles studied medicines holistically, [16][17][18] seven articles investigated medications related to some speci c diseases, [19][20][21][22][23][24][25] and the one remaining assessed the effect of sanctions on air pollution. [26] In terms of method, there were 6 quantitative studies, 4 qualitative studies, and one review (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, poor income, lack of resources, regulatory approval, and high prices are apparently not the only factors that play significant roles in lack of access to AEDs and appropriate epilepsy care. In a recent study, 6 we observed that the hardship by the international economic sanctions imposed on the Iranian people in the past few years caused poor access to AEDs in some patients with epilepsy. Compared to the period before the intensification of sanctions, the price of some AEDs (e.g., levetiracetam) increased up to 300% after intensification of the international economic sanctions.…”
Section: To the Editorsmentioning
confidence: 97%